Cooperativismo, agricultura familiar e mercados institucionais: conceitos, potencialidades e limites - França, Cláudio Viana (2017)
The studied subject of this work is related to the practical effects of the third generation of public policy for family agricultural about the economic organization process of this category. More specifically, it is about the emergence of the family agriculture cooperativism agenda in Minas Gerais. We tried to understand the transformation potential from the economic organization process of rural families, in a broader historical context of the fight for social rights expansion in Brazil, deepening in the democracy and achieving the republican ideal. The theoretical and methodological referential is the historical materialism. From a bibliographic and documentary research, we tried to achieve the unveiling some of interrelations that were stablished between the capital and the work in order to understand how the cooperativism can be inserted in the current historical defense in favor to the agricultural development in Brazil, exploring horizons still not enough discussed related to the institutional public market, family agriculture and the cooperativism. The dissertation is divided in Chapters. In the Chapter 2, a historical contextualization is presented, going through by the capitalism development in Brazil, highlighting in general the developmentalism (from 1950 to 1985) and more in details, the period after the redemocratization (1985-2016). In the developmentalism, the ‘’solution” for the agricultural problem is highlighted, being an important part of the late industrialization, which lead as a consequence to the green revolution, the rural side of the conservative modernization. The political reaction to these consequences lead to the project of agricultural development, that is based in the social security for the workers in the economic familiar regime. In the democratic period, due to the influence of this reaction, were verified an extraordinary increasing in the public policies in the benefit of families. In the Chapter 3, is discuss the emergence of the agenda of cooperativism between the rural workers in economic familiar regime, triggered by the implementation of the third generation family agricultural public policies. However, the employers cooperativism orthodoxies which, obviously, from the point of view of the agricultural development, are not capable to promote the desired transformation. In the opposite, the employer cooperativism reproduce and reinforce the system, consolidating the prevalence of the capital and the structures from the conservative modernization. Conversely, a more aligned form with the interest of the working class in general, was sought, and more specifically, of family agriculture: the workers cooperative. We discussed in this context, the need of internal controls, based in the construction of a democratic institutionalism and in the continuing cooperative liberation education. In the Chapter 4, we search for the historical origins of cooperativism, in the context of the workers fight against the growing industrial capitalism, end of the XVIII century and beginning of XIX century. We tried to understand the forces against which this class was directly confronted in order to understand the logic behind its choices, from where "utopian" socialism originated and the first cooperative experiences. Important classic concepts extracted from this discussion were mobilized in an attempt to understand the potentialities of workers cooperatives in the context of current agricultural development proposals in Brazil, as a way of orienting an approach towards social transformation.